2020
DOI: 10.32872/spb.4415
|View full text |Cite
|
Sign up to set email alerts
|

Self-persuasion increases motivation for social isolation during the COVID-19 pandemic through moral obligation

Abstract: During the COVID-19 pandemic, governments use direct persuasion to encourage social isolation. Since self-persuasion is a more effective method of encouraging behavioural changes, using an experimental approach, we compared direct persuasion to self-persuasion on underlying motivations for voluntary social isolation during the COVID-19 pandemic. We asked the participants (N = 375) to write three arguments in support of social isolation (self-persuasion condition) or to evaluate three government graphics contai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Vaccine hesitancy also significantly decreases when a person knows someone afflicted with COVID-19 (Schwarzinger et al, 2021). Knowing someone who has had COVID-19 is also associated with perceiving the disease as severe (Drążkowski et al, 2020).…”
Section: Reactancementioning
confidence: 96%
“…Vaccine hesitancy also significantly decreases when a person knows someone afflicted with COVID-19 (Schwarzinger et al, 2021). Knowing someone who has had COVID-19 is also associated with perceiving the disease as severe (Drążkowski et al, 2020).…”
Section: Reactancementioning
confidence: 96%
“…Besides the Empathic Sensitivity Scale [39], all the measures were developed based on Francis et al's [40] guideline on creating TPB questionnaires. Those items, to which participants responded using a 7-point Likert scale, were used in prior studies where they presented adequate reliability and validity [17,21]. The following measures were used in both Study 1 and Study 2:…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Baldwin et al [16] demonstrated that self-persuasion might increase parents' intention to vaccinate their adolescent children against human papillomavirus (HPV). Moreover, Dr ą żkowski et al [17] revealed that self-persuasion has a significant effect on one's moral obligation to socially isolate during the COVID-19 pandemic, and through it, on self-isolation intention.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Baldwin et al (2017) demonstrated that self-persuasion might increase parents' intention to vaccinate their adolescent child against Human Papillomavirus (HPV). Moreover, Drążkowski et al (2020) revealed that self-persuasion significantly impacted the moral obligation to socially isolate during the COVID-19 pandemic, and through it on self-isolation intention.…”
Section: Self-persuasionmentioning
confidence: 99%